Literature Review Konsep Dasar dan Manajemen Konflik - Firlyana Zahrotul Mudawamah; Putri Aprilia Daniatul Maulidiyah; Herlina Mustika Sari; M. Tibi Azizi; Mu'alimin Mu'alimin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This article is a literature review that focuses on discussing what is conflict management in schools or madrasah as well as its purpose and function. The research uses a literature study where all information is obtained from articles and books. The discussion and results obtained can be described that conflict management is a force to bring about change and progress in an institution which if utilized in a more productive direction if managed systematically so that it can strengthen cooperative relationships, increase trust and self-esteem, increase creativity and job satisfaction. In order for conflict to have a positive impact on organizational performance and productivity, organizational leaders must have the ability to handle conflict. There are several different approaches available for conflict management, each of which has advantages and disadvantages. Conflict needs to be resolved in a way that is appropriate and relevant to the context of the conflict. The causes of conflict are not only internal to the organization, but also external to the organization.